PERANAN MAHKAMAH KONSTITUSI DALAM MEMUTUSKAN TENTANG PERSELISIHAN HASIL PEMILU PRESIDEN DI INDONESIA (Kajian Pada Pelaksanaan Pemilu Tahun 2014) - NUGROHO, ARY SETIO (Dinamika Hukum, 2015)
The purpose of this study is to examine the role of the Constitutional Court to decide on the dispute results in Indonesian Presidential Election. And explain the obstacles in solving disputes in Indonesian Presidential Election results. This research uses normative legal studies to understand the application of the norms of the law to the facts. The nature of descriptive research study meant to describe a rule of law in the context of theories of law and its implementation, as well as carefully analyze facts about the implementation of legislation in Constitutional Law. The results of the study that the role of the Constitutional Court to decide disputes in the election results, ie when there is a request that the applicant submitted. Decision of the Constitutional Court is the legal basis which gives validity of votes election participants of the calculation results of the general election vote nationally. The Constitutional Court's role is to conduct the examination, then decided to establish the correct sound calculation results of the applicant or by the Election Commission (Article 75 in conjunction with Article 77 Paragraph (3) and (4) of Law No. 4 of 2003). This has relevance as a legal basis to set a general election vote counts nationally with implications for the validity of votes participants election candidates for President and Vice President. Constitutional authority to decide disputes concerning the results of Presidential elections in Indonesia under Article 24C paragraph (1) of the 1945 Constitution, which is explained, that the authority of the Constitutional Court has the authority to hear cases at the first and last decision is final in law against the Constitution, rule on the dispute the authority of state institutions granted by the Constitution, dissolution of political parties and to decide disputes concerning the results of the general election. Barriers in the Presidential election result dispute resolution in Indonesia, among others: 1) the existence of accumulation disputes election results at a certain time. 2) The number of constitutional judges are only nine people, 3) The grace period is quite short dispute resolution, 4) Expansion of the scope of authority of the Court through the decision of the Court itself, 5) Not terjadwalnya good election and election schedule integration with other systems. 6) There MK maximum support device in resolving disputed election results. Keywords: Role, the Constitutional Court, Decide, Dispute Presidential Election